2006
DOI: 10.1111/j.1365-2605.2005.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant impact of 5α‐reductase type 2 polymorphisms on sperm concentration and motility

Abstract: Androgens, including 5alpha-dihydrotestosterone (DHT), are known to play a role for spermatogenesis and accessory sex gland function. The enzyme 5alpha-reductase (SRD5A) catalyses the conversion of testosterone to DHT. Our objective was to investigate whether polymorphisms in the SRD5A2 gene influence semen parameters in the general population. DNA from 182 Swedish military conscripts was examined for the A49T, V89L, and R227Q polymorphisms in the SRD5A type 2 gene. Ejaculates were analysed according to WHO gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
2
15
2
Order By: Relevance
“…In their study, Elzanaty et al investigated the effect of SRD5A2 polymorphisms on sperm parameters in Swedish military conscripts. Their results showed that variants of A49T and V89L are associated with sperm concentration and motility, respectively (29). Our results are not in agreement with those authors in that the mutation at rs632148 demonstrated an association with sperm motility, but not the rs523349 (V89L) mutation.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…In their study, Elzanaty et al investigated the effect of SRD5A2 polymorphisms on sperm parameters in Swedish military conscripts. Their results showed that variants of A49T and V89L are associated with sperm concentration and motility, respectively (29). Our results are not in agreement with those authors in that the mutation at rs632148 demonstrated an association with sperm motility, but not the rs523349 (V89L) mutation.…”
contrasting
confidence: 57%
“…The A49T mutation was associated with a significantly higher sperm concentration (29). Both of these findings indicate the role of SRD5A2 on spermatogenesis.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…[1,7,[9][10][11][12][13] Si additions can reduce the density and coefficient of thermal expansion, and improve the mechanical properties, which include the modulus, strength, hardness and wear resistance of Al alloys; however, the ductility decreases with an increase of Si level. [9][10][11] The mechanical properties of Al-Si alloys are also determined by the morphology of the Si particle. Si in a needle shape will result in a poor ductility.…”
Section: Introductionmentioning
confidence: 99%
“…If administered in utero, external genitalia were feminized in rats (ImperatoMcGinley et al 1992) or developed abnormalities in rhesus monkeys (Prahalada et al 1997). Humans with deficiency of Srd5a2 developed feminized genitalia (Imperato-McGinley et al 1981), and polymorphisms in Srd5a2 gene were associated with differences in sperm concentration and motility (Elzanaty et al 2006). …”
Section: Introductionmentioning
confidence: 99%